2011
DOI: 10.3109/15569527.2011.554480
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress impairs endothelial nitric oxide levels in Behçets’ disease

Abstract: Decreased NO levels mediated by increased oxidative stress significantly contribute to endothelial dysfunction observed in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…In vitro studies have revealed that the major cause related with the etiopathogenesis in patients with BD is induction of endothelial cells by oxidative stress. 9,10 Endocan is a dermatan sulphate proteoglycan molecule. It is an endothelial marker expressed by endothelial cells.…”
mentioning
confidence: 99%
“…In vitro studies have revealed that the major cause related with the etiopathogenesis in patients with BD is induction of endothelial cells by oxidative stress. 9,10 Endocan is a dermatan sulphate proteoglycan molecule. It is an endothelial marker expressed by endothelial cells.…”
mentioning
confidence: 99%
“…Decreased activity of NO (also known as endothelium-derived relaxing factor) leads to vasoconstriction, monocyte adhesion, and platelet aggregation, which may lead to vascular dysfunction, separately or in combination, seen in BD [18]. Along with increased serum ADMA levels, lower NO levels have been reported to be a significant contributor to ED observed in BD [19][20][21]. Both the inhibition of NO synthase by ADMA and oxidant/ antioxidant imbalance may contribute to decreased bioavailability of NO in BD.…”
Section: Discussionmentioning
confidence: 92%
“…Endogenous NO, produced by endothelial cells, is known for its multiple effects, such as vasodilative, antiplatelet and antiproliferative ones [67]. NO levels are reported to be low in BD patients compared to the healthy population, especially in patients with active BD.…”
Section: The Central Role Of Blood Vessel Endothelium In Vasculitis-amentioning
confidence: 99%